Hydroisomerization catalyst and application thereof in n-alkane isomerization reaction
By modifying SAPO-11 zeolite with Ni and loading it with WS2, the problems of high diffusion resistance and easy poisoning of precious metals in traditional SAPO-11 zeolite were solved, and a hydrogenation isomerization catalyst with high catalytic activity and isomerization selectivity was achieved, thereby improving the catalytic performance.
Patent Information
- Application Number
- CN202510626327.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-15
- Publication Date
- 2025-09-12
AI Technical Summary
The application of traditional SAPO-11 molecular sieve in hydroisomerization catalysts has the problem that the micropore size leads to large diffusion resistance of reaction product molecules, low catalytic activity and isomerization selectivity. At the same time, precious metal catalysts are expensive and easily poisoned, and the non-precious metal Ni has low dispersion, resulting in insufficient catalytic activity and selectivity.
Ni-modified SAPO-11 molecular sieve was used to prepare a hydroisomerization catalyst with excellent catalytic activity and hydroisomerization selectivity by adjusting its pore size to 5.4-14.5 nm, increasing the dispersion to 0.31-0.40, and loading the average stacking number of WS2 phase to 1.8-3.5.
The specific surface area and pore volume of the molecular sieve are increased, the diffusion resistance of alkane molecules in the molecular sieve is reduced, the dispersion of Ni is promoted, and the isomerization selectivity and performance of the catalyst are improved.
Smart Images

Figure CN120618524A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hydroisomerization catalysts, and in particular relates to a hydroisomerization catalyst and application thereof in the isomerization reaction of normal paraffins. Background Art
[0002] As demand for petroleum products in high-altitude and cold regions continues to increase, the use of conventional oils has been significantly limited, and the production of low-freezing-point oils has become a pressing issue. High levels of long-chain n-alkanes lead to a higher pour point in diesel and poor low-temperature fluidity in lubricant base oils. To address this conflict, hydrogenation and isomerization of n-alkanes into isoalkanes with similar or similar molecular weights can improve low-temperature fluidity, such as the freezing point of kerosene, the freezing point and cold filter plugging point of diesel, and the pour point of lubricant base oils.
[0003] SAPO-11 molecular sieve is a weakly acidic support with an AEL structure and a one-dimensional pore structure, with a pore size of 0.39 nm × 0.64 nm. Its unique 10-membered ring elliptical straight pore structure and mild acidity make it an ideal support for hydroisomerization catalysts. However, the application of conventional SAPO-11 molecular sieves in hydroisomerization catalysts still has certain limitations. Its micropore size results in high diffusion resistance of reaction product molecules within the pores, resulting in low catalytic activity and isomerization selectivity in hydrocarbon isomerization reactions.
[0004] Precious metals have significant catalytic activity as metal components of hydroisomerization catalysts, but there are the following problems. On the one hand, the high cost of precious metals limits their industrial application; on the other hand, precious metals are poisoned and deactivated due to their sensitivity to sulfur compounds in the raw materials. Some researchers use non-precious metal Ni instead of precious metals to prepare hydrocarbon hydroisomerization catalysts, which greatly reduces the preparation cost of the catalyst, and Ni has good hydroisomerization / dehydrogenation activity. However, the Ni particle size is large (20-30nm) and the dispersion is low, which greatly reduces the catalytic activity of the catalyst and the selectivity of hydroisomerization. Therefore, it is necessary to provide a new hydroisomerization catalyst to improve the above problems. Summary of the Invention
[0005] In order to solve the above technical problems, the object of the present invention is to provide a hydroisomerization catalyst and its application in the isomerization reaction of normal paraffins, wherein the catalyst has excellent catalytic activity and hydroisomerization selectivity.
[0006] In order to achieve the above object, the present invention provides a hydroisomerization catalyst, which comprises a Ni-modified SAPO-11 molecular sieve and an active component supported thereon; the Ni-modified SAPO-11 molecular sieve has a pore size of 5.4 to 14.5 nm, a Ni dispersion of 0.31 to 0.40, and a specific surface area of 195 to 288 m 2 / g.
[0007] Furthermore, the pore volume of Ni-modified SAPO-11 molecular sieve is 0.27-0.5m 3 / g.
[0008] Furthermore, the non-noble metals are Ni and W.
[0009] Furthermore, the average stacking layer number of WS2 phase is 1.8 to 3.5, and the length of WS2 lamellae is 2.60 to 4.75 nm.
[0010] In a preferred embodiment, the hydroisomerization catalyst is prepared by the following steps: the hydroisomerization catalyst is prepared by the following steps: mixing a first nickel source, a first phosphorus source, a first aluminum source and water to form gel A1; adding a first structure directing agent and a first silicon source to gel A1 to form gel B1, subjecting gel B1 to a first crystallization, and subjecting the product after the first crystallization to a first drying and a first calcination to obtain a Ni-modified SAPO-11 molecular sieve; using a first nickel-containing soluble salt solution and a first tungsten-containing soluble salt solution to a first impregnation of the Ni-modified SAPO-11 molecular sieve, and subjecting the product after the first impregnation to a second drying and a second calcination to obtain a hydroisomerization catalyst; wherein the first nickel source is calculated as NiO, the first aluminum source is calculated as Al2O3, and the weight ratio of the first nickel source to the first aluminum source is 0.01-0.04:1.0, preferably 0.03-0.04:1.0.
[0011] In another preferred embodiment, the hydroisomerization catalyst is prepared by the following steps: mixing a second phosphorus source, a second aluminum source and water to form a gel A2; adding a second structure directing agent and a second silicon source to the gel A2 to form a gel B2; subjecting the gel B2 to a second crystallization; and subjecting the product after the second crystallization to a third drying and a third calcination to obtain an intermediate product C2; subjecting the second nickel source and the intermediate product C2 to an ion exchange, and subjecting the product after the ion exchange to a fourth drying and a fourth calcination to obtain a Ni-modified SAPO-11 molecular sieve; using a second nickel-containing soluble salt solution and a second tungsten-containing soluble salt solution to a second impregnation of the Ni-modified SAPO-11 molecular sieve, and subjecting the product after the second impregnation to a fifth drying and a fifth calcination to obtain a hydroisomerization catalyst; wherein the ion exchange treatment temperature is 70-95°C, and the treatment time is 4-6h; the second nickel source is calculated as NiO, the second aluminum source is calculated as Al2O3, and the weight ratio of the second nickel source to the second aluminum source is 0.1-0.3:1.0.
[0012] In another preferred embodiment, the hydroisomerization catalyst is prepared by the following steps: the hydroisomerization catalyst is prepared by the following steps: mixing a third phosphorus source, a third aluminum source, and water to form gel A3; adding a third structure directing agent and a third silicon source to gel A3 to form gel B3; subjecting gel B3 to a third crystallization; and subjecting the product after the third crystallization to a sixth drying and a sixth calcination to obtain an intermediate product C3; and subjecting the intermediate product C3 to a third impregnation with a dispersion containing ethylenediaminetetraacetic acid and a third nickel source, and subjecting the product after the third impregnation to a third impregnation. A seventh drying and a seventh calcination are performed to obtain a Ni-modified SAPO-11 molecular sieve; a third nickel-containing soluble salt solution and a third tungsten-containing soluble salt solution are used to perform a fourth impregnation on the Ni-modified SAPO-11 molecular sieve, and the product after the fourth impregnation is subjected to an eighth drying and an eighth calcination to obtain a hydroisomerization catalyst; wherein the impregnation temperature of the third impregnation is 20-40°C, and the impregnation time is 4-6 hours; the third nickel source is calculated as NiO, and the weight ratio of ethylenediaminetetraacetic acid, the third nickel source and the intermediate product C3 is 2-4:0.04-0.12:1.
[0013] Furthermore, the first nickel source, the second nickel source and the third nickel source each independently include one or a combination of two or more of nickel nitrate, nickel acetate and nickel chloride, preferably nickel nitrate.
[0014] Furthermore, the first phosphorus source, the second phosphorus source and the third phosphorus source each independently include one or a combination of two or more of phosphoric acid, phosphorous acid and hypophosphorous acid, preferably phosphoric acid.
[0015] Furthermore, the first aluminum source, the second aluminum source and the third aluminum source each independently include one or a combination of two or more of pseudo-boehmite, sodium aluminate, aluminum sulfate and aluminum isopropoxide, preferably including pseudo-boehmite and / or aluminum isopropoxide.
[0016] Furthermore, the first structure directing agent, the second structure directing agent and the third structure directing agent each independently include one or a combination of two or more of di-n-propylamine, diisopropylamine, dimethylamine and diethylamine, preferably include di-n-propylamine and / or diisopropylamine.
[0017] Furthermore, the first silicon source, the second silicon source and the third silicon source each independently include one or a combination of two or more of silica sol, silicon dioxide and tetraethyl orthosilicate, preferably silica sol and / or silicon dioxide.
[0018] Furthermore, the first, second, and third crystallization steps each independently include a first, second, and third crystallization step performed sequentially. The first crystallization step has a treatment temperature of 60-110°C and a treatment time of 12-14 hours; the second crystallization step has a treatment temperature of 120-150°C and a treatment time of 10-14 hours; and the third crystallization step has a treatment temperature of 160-230°C and a treatment time of 10-14 hours. Based on the three-step crystallization process described above, nucleation is promoted by lowering the crystallization temperature, thereby reducing grain size.
[0019] Furthermore, the treatment temperatures of the first drying, the third drying and the sixth drying are each independently 70 to 120° C., and the treatment times of the first drying, the third drying and the sixth drying are each independently 4 to 12 hours.
[0020] Furthermore, the treatment temperatures of the first calcination, the third calcination and the sixth calcination are each independently 500-700° C., and the treatment times of the first calcination, the third calcination and the sixth calcination are each independently 4-12 hours.
[0021] Furthermore, the treatment temperatures of the second drying, the fifth drying and the eighth drying are each independently 100 to 120° C., and the treatment times of the second drying, the fifth drying and the eighth drying are each independently 12 to 24 hours.
[0022] Furthermore, the treatment temperatures of the second calcination, the fifth calcination and the eighth calcination are each independently 500-700° C., and the treatment times of the second calcination, the fifth calcination and the eighth calcination are each independently 4-12 hours.
[0023] Furthermore, the treatment temperatures of the fourth drying and the seventh drying are each independently 80 to 120° C., and the treatment times are each independently 12 to 24 hours.
[0024] Furthermore, the fourth calcination process is performed at a temperature of 500 to 600° C. and for a time of 4 to 8 hours.
[0025] Furthermore, the treatment temperature of the seventh calcination is independently 500-650° C., and the treatment time is 4-8 hours.
[0026] Furthermore, the first impregnation, the second impregnation, the third impregnation and the fourth impregnation are each independently an equal volume impregnation.
[0027] Furthermore, the first aluminum source, the second aluminum source and the third aluminum source are calculated as Al2O3, the first phosphorus source, the second phosphorus source and the third phosphorus source are calculated as P2O5, the first silicon source, the second silicon source and the third silicon source are calculated as SiO2, the molar ratio of the first aluminum source, the first phosphorus source, the first silicon source and the first structure directing agent is 1.0:0.5~1.5:0.2~2.5:0.5~2.0, the molar ratio of the second aluminum source, the second phosphorus source, the second silicon source and the second structure directing agent is 1.0:0.5~1.5:0.2~2.5:0.5~2.0, and the molar ratio of the third aluminum source, the third phosphorus source, the third silicon source and the third structure directing agent is 1.0:0.5~1.5:0.2~2.5:0.5~2.0.
[0028] Furthermore, calculated as NiO, the content of nickel metal atoms in the first nickel-containing soluble salt solution, the second nickel-containing soluble salt solution and the third nickel-containing soluble salt solution is each independently 2 to 6 wt%; calculated as WO3, the content of tungsten metal atoms in the first tungsten-containing soluble salt solution, the second tungsten-containing soluble salt solution and the first tungsten-containing soluble salt solution is each independently 4 to 15 wt%.
[0029] The present invention also provides an application of the aforementioned hydroisomerization catalyst in the isomerization reaction of normal paraffins. Furthermore, the reaction temperature of the normal paraffin isomerization reaction is 280-450°C, the reaction pressure is 2-5 MPa, the volume ratio of hydrogen to normal paraffins is 400-700:1, and the liquid space velocity is 1-6 h -1 .
[0030] The present invention has the following beneficial effects: on the one hand, it modifies the pore structure of the SAPO-11 molecular sieve, increasing the specific surface area and pore volume of the molecular sieve, reducing the diffusion resistance of alkane molecules in the molecular sieve, and providing more surface area for reaction; on the other hand, it promotes the dispersion of the loaded metallic Ni, promoting more Ni species to form the hydrogenation / dehydrogenation active phase. The hydroisomerization catalyst provided by the present invention has high isomerization selectivity and exhibits excellent isomerization performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 XRD spectra of Ni-modified SAPO-11 molecular sieves in Comparative Examples 1-3 and Examples 1-5.
[0032] Figure 2 2 are the N2 adsorption-desorption isotherms of the Ni-modified SAPO-11 molecular sieves in Comparative Examples 1-3 and Examples 3-5. DETAILED DESCRIPTION
[0033] In order to have a clearer understanding of the technical features, objectives and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be understood as limiting the scope of implementation of the present invention.
[0034] Example 1
[0035] This embodiment provides a method for preparing a NiW / 2NiSAPO-11 catalyst, which comprises:
[0036] A certain amount of nickel nitrate hexahydrate (nickel nitrate hexahydrate is calculated as NiO, pseudo-boehmite is calculated as Al2O3, and the mass ratio of NiO to Al2O3 is 0.02:1), 13.78 g of phosphoric acid (AR, 85%), 64.56 g of deionized water and 9.662 g of n-propanol (AR, 99%) were stirred and mixed to form a solution, and then 11 g of pseudo-boehmite (AR, 70%) was added to the obtained solution and stirred for 2 hours to form gel A1.
[0037] 4.025 g of di-n-propylamine (CP, 98%) and 4.025 g of diisopropylamine (CP, 98%) were added to gel A1 under stirring and stirred continuously for 2 h. Then, 7.17 g of acidic silica sol (30 wt% SiO2) was slowly added and stirred vigorously for 2 h to form gel B1.
[0038] Gel B1 was transferred to a polytetrafluoroethylene reactor for crystallization. The first stage crystallization temperature was 90°C and the crystallization time was 12 h; the second stage crystallization temperature was 140°C and the crystallization time was 12 h; the third stage crystallization temperature was 190°C and the crystallization time was 12 h.
[0039] The crystallized product was taken out, the solid product was separated, filtered, washed, dried at 110 ° C for 12 h, and calcined at 600 ° C for 8 h to obtain 2NiSAPO-11 molecular sieve. The XRD and BET data results are shown in Figure 1 and Table 1.
[0040] The above-mentioned 2NiSAPO-11 molecular sieve was impregnated with equal volumes of nickel nitrate hexahydrate with a NiO content of 4wt% and ammonium metatungstate hydrate (AR, 99.5wt%) with a WO3 content of 12wt%. After impregnation, the catalyst was dried at 110°C for 12h and calcined at 500°C for 4h to obtain a NiW / 2NiSAPO-11 catalyst. The HRTEM data results are shown in Table 2.
[0041] Hydrocarbon hydroisomerization test: using n-hexadecane as the model raw material, the temperature is 360℃, the H2 pressure is 3MPa, the volume ratio of hydrogen to n-hexadecane is 400:1, and the liquid space velocity is 2h -1 The catalyst reaction results are shown in Table 3.
[0042] Example 2
[0043] This embodiment provides a method for preparing a NiW / 3NiSAPO-11 catalyst, which comprises:
[0044] A certain amount of nickel nitrate hexahydrate (nickel nitrate hexahydrate is calculated as NiO, pseudo-boehmite is calculated as Al2O3, and the mass ratio of NiO to Al2O3 is 0.03:1), 13.78 g of phosphoric acid (AR, 85%), 64.56 g of deionized water and 9.662 g of n-propanol (AR, 99%) were stirred and mixed to form a solution, and then 11 g of pseudo-boehmite (AR, 70%) was added to the obtained solution and stirred for 2 hours to form gel A1.
[0045] 4.025 g of di-n-propylamine (CP, 98%) and 4.025 g of diisopropylamine (CP, 98%) were added to gel A1 under stirring and stirred continuously for 2 h. Then, 7.17 g of acidic silica sol (30 wt% SiO2) was slowly added and stirred vigorously for 2 h to form gel B1.
[0046] Gel B1 was transferred to a polytetrafluoroethylene reactor for crystallization. The first stage crystallization temperature was 90°C and the crystallization time was 12 h; the second stage crystallization temperature was 140°C and the crystallization time was 12 h; the third stage crystallization temperature was 190°C and the crystallization time was 12 h.
[0047] The crystallized product was taken out, the solid product was separated, filtered, washed, dried at 110°C for 12 hours, and calcined at 600°C for 8 hours. 3NiSAPO-11 molecular sieve was obtained, and its XRD and BET data results are shown in Figure 1 and Table 1.
[0048] The above-mentioned 3NiSAPO-11 molecular sieve was impregnated with equal volumes of nickel nitrate hexahydrate with a NiO content of 4wt% and ammonium metatungstate hydrate (AR, 99.5wt%) with a WO3 content of 12wt%, dried at 110°C for 12h, and calcined at 500°C for 4h to obtain a NiW / 3NiSAPO-11 catalyst. The HRTEM data results are shown in Table 2.
[0049] Hydrocarbon hydroisomerization test: using n-hexadecane as the model raw material, the temperature is 360℃, the H2 pressure is 3MPa, the volume ratio of hydrogen to n-hexadecane is 400:1, and the liquid space velocity is 2h -1 The catalyst reaction results are shown in Table 3.
[0050] Example 3
[0051] This embodiment provides a method for preparing a NiW / 4NiSAPO-11 catalyst, which comprises:
[0052] A certain amount of nickel nitrate hexahydrate (nickel nitrate hexahydrate is calculated as NiO, pseudo-boehmite is calculated as Al2O3, and the mass ratio of NiO to Al2O3 is 0.04:1), 13.78 g of phosphoric acid (AR, 85%), 64.56 g of deionized water and 9.662 g of n-propanol (AR, 99%) were stirred and mixed to form a solution. Then, 11 g of pseudo-boehmite (AR, 70%) was added to the obtained solution and stirred for 2 hours to form gel A1.
[0053] 4.025 g of di-n-propylamine (CP, 98%) and 4.025 g of diisopropylamine (CP, 98%) were added to gel A1 under stirring and stirred continuously for 2 h. Then, 7.17 g of acidic silica sol (30 wt% SiO2) was slowly added and stirred vigorously for 2 h to form gel B1.
[0054] Gel B1 was transferred to a polytetrafluoroethylene reactor for crystallization. The first stage crystallization temperature was 90°C and the crystallization time was 12 h; the second stage crystallization temperature was 140°C and the crystallization time was 12 h; the third stage crystallization temperature was 190°C and the crystallization time was 12 h.
[0055] The crystallized product was taken out, the solid product was separated, filtered, washed, dried at 110°C for 12 hours, and calcined at 600°C for 8 hours. 4NiSAPO-11 molecular sieve was obtained, and its XRD and BET data results are shown in Figure 1 、 Figure 2 and Table 1.
[0056] The above-mentioned 4NiSAPO-11 molecular sieve was impregnated with equal volumes of nickel nitrate hexahydrate with a NiO content of 4wt% and ammonium metatungstate hydrate (AR, 99.5wt%) with a WO3 content of 12wt%, dried at 110°C for 12h, and calcined at 500°C for 4h to obtain a NiW / 4NiSAPO-11 catalyst. The HRTEM data results are shown in Table 2.
[0057] Hydrocarbon hydroisomerization test: using n-hexadecane as the model raw material, the temperature is 360℃, the H2 pressure is 3MPa, the volume ratio of hydrogen to n-hexadecane is 400:1, and the liquid space velocity is 2h -1 The catalyst reaction results are shown in Table 3.
[0058] Example 4
[0059] This embodiment provides a method for preparing a NiW / Ni&SAPO-11 catalyst, which comprises:
[0060] 13.78 g of phosphoric acid (AR, 85%), 64.56 g of deionized water and 9.662 g of n-propanol (AR, 99%) were stirred and mixed to form a solution, and then 11 g of pseudo-boehmite (AR, 70%) was added to the obtained solution and stirred for 2 h to form gel A2.
[0061] 4.025 g of di-n-propylamine (CP, 98%) and 4.025 g of diisopropylamine (CP, 98%) were added to gel A2 under stirring and stirred continuously for 2 h. Then, 7.17 g of acidic silica sol (30 wt% SiO2) was slowly added and stirred vigorously for 2 h to form gel B2.
[0062] Gel B2 was transferred to a polytetrafluoroethylene reactor for crystallization. The first crystallization stage was at 90°C for 12 hours; the second crystallization stage was at 140°C for 12 hours; and the third crystallization stage was at 190°C for 12 hours. The crystallized product was removed, the solid product was separated, filtered, washed, dried at 110°C for 12 hours, and calcined at 600°C for 8 hours. This yielded SAPO-11 molecular sieve.
[0063] Weigh 10.0g of the above SAPO-11 molecular sieve and mix it with 100g of 0.3mol / L nickel nitrate solution (the nickel nitrate solution is calculated as NiO, and the mass ratio of NiO to SAPO-11 molecular sieve is 0.22:1). Exchange at 90℃ for 4h. Filter and wash, dry at 110℃ for 12h, and calcine at 500℃ for 4h to obtain Ni&SAPO-11 molecular sieve. Its XRD and BET data results are shown in Figure 1 、 Figure 2 and Table 1.
[0064] The Ni & SAPO-11 molecular sieve was impregnated with equal volumes of nickel nitrate hexahydrate with a NiO content of 4 wt% and ammonium metatungstate hydrate (AR, 99.5 wt%) with a WO3 content of 12 wt%, dried at 110 ° C for 12 h, and calcined at 500 ° C for 4 h to obtain a NiW / Ni & SAPO-11 catalyst. The HRTEM data results are shown in Table 2.
[0065] Hydrocarbon hydroisomerization test: using n-hexadecane as the model raw material, the temperature is 360℃, the H2 pressure is 3MPa, the volume ratio of hydrogen to n-hexadecane is 400:1, and the liquid space velocity is 2h -1 The catalyst reaction results are shown in Table 3.
[0066] Example 5
[0067] This embodiment provides a method for preparing a NiW / Ni-SAPO-11 catalyst, which comprises:
[0068] 13.78 g of phosphoric acid (AR, 85%), 64.56 g of deionized water and 9.662 g of n-propanol (AR, 99%) were stirred to form a solution, and then 11 g of pseudo-boehmite (AR, 70%) was added to the obtained solution and stirred for 2 h to form gel A.
[0069] 4.025 g of di-n-propylamine (CP, 98%) and 4.025 g of diisopropylamine (CP, 98%) were added to gel A under stirring and stirred continuously for 2 h. Then, 7.17 g of acidic silica sol (30 wt% SiO2) was slowly added and stirred vigorously for 2 h to form gel B.
[0070] Gel B was transferred to a polytetrafluoroethylene reactor for crystallization. The first crystallization stage was at 90°C for 12 hours; the second crystallization stage was at 140°C for 12 hours; and the third crystallization stage was at 190°C for 12 hours. The crystallized product was removed, the solid product was separated, filtered, washed, dried at 110°C for 12 hours, and calcined at 600°C for 8 hours. This yielded SAPO-11 molecular sieve.
[0071] 0.1 mol of EDTA was added to 0.05 L of 0.3 mol / L nickel nitrate solution to form an impregnation solution, and 10 g of the above-mentioned SAPO-11 molecular sieve was impregnated with the impregnation solution (the nickel nitrate solution was calculated as NiO, and the mass ratio of EDTA:NiO:SAPO-11 molecular sieve was 2.92:0.11:1). The mixture was filtered and washed, dried at 110 ° C for 12 h, and calcined at 500 ° C for 4 h to obtain Ni-SAPO-11 molecular sieve. Its XRD and BET data results are shown in Figure 1 、 Figure 2 and Table 1.
[0072] The Ni-SAPO-11 molecular sieve was impregnated with equal volumes of nickel nitrate hexahydrate with a NiO content of 4 wt% and ammonium metatungstate hydrate (AR, 99.5 wt%) with a WO3 content of 12 wt%, dried at 110°C for 12 h, and calcined at 500°C for 4 h to obtain a NiW / Ni-SAPO-11 catalyst. The HRTEM data results are shown in Table 2.
[0073] Hydrocarbon hydroisomerization test: using n-hexadecane as the model raw material, the temperature is 360℃, the H2 pressure is 3MPa, the volume ratio of hydrogen to n-hexadecane is 400:1, and the liquid space velocity is 2h -1 The catalyst reaction results are shown in Table 3.
[0074] Comparative Example 1
[0075] This comparative example provides a method for preparing a NiW / SAPO-11-N catalyst. The difference between this comparative example 1 and implementation examples 1-3 is that the segmented three-step crystallization is changed to a one-step crystallization, and Ni in-situ modification is not performed. The preparation method comprises:
[0076] 13.78 g of phosphoric acid (AR, 85%), 64.56 g of deionized water and 9.662 g of n-propanol (AR, 99%) were stirred to form a solution, and then 11 g of pseudo-boehmite (AR, 70%) was added to the obtained solution and stirred for 2 h to form gel A.
[0077] 4.025 g of di-n-propylamine (CP, 98%) and 4.025 g of diisopropylamine (CP, 98%) were added to gel A under stirring and stirred continuously for 2 h. Then, 7.17 g of acidic silica sol (30% SiO2) was slowly added and stirred vigorously for 2 h to form gel B.
[0078] Gel B was transferred to a polytetrafluoroethylene reactor with a crystallization temperature of 190°C and a crystallization time of 36 h.
[0079] The crystallized product was taken out, the solid product was separated, filtered, washed, dried at 110°C for 12 hours, and calcined at 600°C for 8 hours. Conventional SAPO-11-N molecular sieve was obtained, and its XRD and BET data results are shown in Figure 1 、 Figure 2 and Table 1.
[0080] The above-mentioned SAPO-11-N molecular sieve was impregnated with equal volumes of nickel nitrate hexahydrate with a NiO content of 4wt% and ammonium metatungstate hydrate (AR, 99.5wt%) with a WO3 content of 12wt%, dried at 110°C for 12h, and calcined at 500°C for 4h to obtain a NiW / SAPO-11-N catalyst. The HRTEM data results are shown in Table 2.
[0081] Hydrocarbon hydroisomerization test: using n-hexadecane as the model raw material, the temperature is 360℃, the H2 pressure is 3MPa, the volume ratio of hydrogen to hydrocarbon is 400:1, and the liquid space velocity is 2h -1 The catalyst reaction results are shown in Table 3.
[0082] Comparative Example 2
[0083] This comparative example provides a preparation method of a NiW / SAPO-11 catalyst. The difference between this comparative example and Examples 1-3 is that Ni is not modified in situ. The preparation method comprises:
[0084] 13.78 g of phosphoric acid (AR, 85%), 64.56 g of deionized water and 9.662 g of n-propanol (AR, 99%) were stirred to form a solution, and then 11 g of pseudo-boehmite (AR, 70%) was added to the obtained solution and stirred for 2 h to form gel A.
[0085] 4.025 g of di-n-propylamine (CP, 98%) and 4.025 g of diisopropylamine (CP, 98%) were added to gel A under stirring and stirred continuously for 2 h. Then, 7.17 g of acidic silica sol (30% SiO2) was slowly added and stirred vigorously for 2 h to form gel B.
[0086] Gel B was transferred to a polytetrafluoroethylene reactor for crystallization. The first stage crystallization temperature was 90°C and the crystallization time was 12 h; the second stage crystallization temperature was 140°C and the crystallization time was 12 h; the third stage crystallization temperature was 190°C and the crystallization time was 12 h.
[0087] The crystallized product was taken out, the solid product was separated, filtered, washed, dried at 110°C for 12 hours, and calcined at 600°C for 8 hours. Conventional SAPO-11 molecular sieve was obtained, and its XRD and BET data results are shown in Figure 1 、 Figure 2 and Table 1.
[0088] The above-mentioned SAPO-11 molecular sieve was impregnated with equal volumes of nickel nitrate hexahydrate with a NiO content of 4wt% and ammonium metatungstate hydrate (AR, 99.5wt%) with a WO3 content of 12wt%, dried at 110°C for 12h, and calcined at 500°C for 4h to obtain a NiW / SAPO-11 catalyst. The HRTEM data results are shown in Table 2.
[0089] Hydrocarbon hydroisomerization test: using n-hexadecane as the model raw material, the temperature is 360℃, the H2 pressure is 3MPa, the volume ratio of hydrogen to hydrocarbon is 400:1, and the liquid space velocity is 2h -1 The catalyst reaction results are shown in Table 3.
[0090] Comparative Example 3
[0091] This comparative example provides a preparation method of a NiW / SAPO-11-Ni catalyst. Comparative Example 3 is a conventional Ni modification method. The preparation method includes:
[0092] 13.78 g of phosphoric acid (AR, 85%), 64.56 g of deionized water and 9.662 g of n-propanol (AR, 99%) were stirred to form a solution, and then 11 g of pseudo-boehmite (AR, 70%) was added to the obtained solution and stirred for 2 h to form gel A.
[0093] 4.025 g of di-n-propylamine (CP, 98%) and 4.025 g of diisopropylamine (CP, 98%) were added to gel A under stirring and stirred continuously for 2 h. Then, 7.17 g of acidic silica sol (30% SiO2) was slowly added and stirred vigorously for 2 h to form gel B.
[0094] Gel B was transferred to a polytetrafluoroethylene reactor for crystallization. The first stage crystallization temperature was 90°C and the crystallization time was 12 h; the second stage crystallization temperature was 140°C and the crystallization time was 12 h; the third stage crystallization temperature was 190°C and the crystallization time was 12 h.
[0095] The crystallized product was taken out, and the solid product was separated, filtered, washed, dried at 110° C. for 12 h, and calcined at 600° C. for 8 h to obtain SAPO-11 molecular sieve.
[0096] Prepare 0.05L 0.3mol / L nickel nitrate solution, and impregnate 10g SAPO-11 molecular sieve with equal volume to obtain SAPO-11-Ni molecular sieve. Its XRD and BET data results are shown in Figure 1 、 Figure 2 and Table 1.
[0097] The above-mentioned SAPO-11-Ni molecular sieve was impregnated with equal volumes of nickel nitrate hexahydrate with a NiO content of 4wt% and ammonium metatungstate hydrate (AR, 99.5wt%) with a WO3 content of 12wt%, dried at 110°C for 12h, and calcined at 500°C for 4h to obtain a NiW / SAPO-11-Ni catalyst. The HRTEM data results are shown in Table 2.
[0098] Hydrocarbon hydroisomerization test: using n-hexadecane as the model raw material, the temperature is 360℃, the H2 pressure is 3MPa, the volume ratio of hydrogen to hydrocarbon is 400:1, and the liquid space velocity is 2h -1 The catalyst reaction results are shown in Table 3.
[0099] Table 1
[0100] Serial number sample <![CDATA[S BET (m 2 / g)]]> <![CDATA[V total (cm 3 / g)]]> Pore diameter (nm) Comparative Example 1 SAPO-11-N 193.56 0.21 4.91 Comparative Example 2 SAPO-11 200.56 0.25 5.10 Comparative Example 3 SAPO-11-Ni 187.19 0.26 5.27 Example 1 2NiSAPO-11 207.10 0.27 5.47 Example 2 3NiSAPO-11 214.73 0.31 5.94 Example 3 4NiSAPO-11 222.85 0.36 6.46 Example 4 Ni&SAPO-11 195.44 0.27 10.19 Example 5 Ni-SAPO-11 287.60 0.28 14.24
[0101] As can be seen from the test data in Table 1, compared with Comparative Examples 1-3, the sample in Example 3 has a larger pore volume, pore diameter and specific surface area, indicating that the Ni in situ modification method is conducive to the increase of specific surface area and pore volume and pore diameter, providing more reaction surface. Compared with Comparative Examples 1-3, the specific surface area and pore volume of the sample in Example 4 are less improved, and the pore diameter is increased. It is possible that some Ni species occupy the pores during ion exchange. Compared with Comparative Examples 1-3, the specific surface area, pore volume and pore diameter of the sample in Example 5 are greatly improved, indicating that ethylenediaminetetraacetic acid in the complex excess impregnation method has the ability to reorganize and create new pores, which can better improve the pore volume, pore diameter and specific surface area of the sample.
[0102] Table 2
[0103] Serial number catalyst Platelet length (nm) Number of stacking layers <![CDATA[Dispersion f w > Comparative Example 1 NiW / SAPO-11-N 4.71 1.32 0.27 Comparative Example 2 NiW / SAPO-11 4.57 1.39 0.30 Comparative Example 3 NiW / SAPO-11-Ni 4.46 1.63 0.30 Example 1 NiW / 2NiSAPO-11 4.23 1.85 0.31 Example 2 NiW / 3NiSAPO-11 4.06 2.18 0.32 Example 3 NiW / 4NiSAPO-11 3.82 2.53 0.40 Example 4 NiW / / Ni&SAPO-11 3.15 3.32 0.35 Example 5 NiW / Ni-SAPO-11 2.69 3.37 0.36
[0104] In order to observe the morphology and dispersibility of the NiWS active phase, the morphology of the sulfided catalyst was studied by HRTEM. As can be seen from Table 2, relative to Comparative Example 2, the platelet dispersion of each material in Examples 3-5 shows an increasing trend in the order of NiW / Ni-SAPO-11>NiW / Ni@SAPO-11>NiW / 4NiSAPO-11>NiW / SAPO-11, indicating that the in-situ modification method, ion exchange method, and complex over-impregnation modification method can all improve the dispersion of the active metal; at the same time, the WS2 platelet length of each catalyst in Examples 3-5 shows a decreasing trend in the order of NiW / Ni-SAPO-11<NiW / Ni@SAPO-11<NiW / 4NiSAPO-11<NiW / SAPO-11, which is exactly consistent with the increasing trend of platelet dispersion. Compared with Comparative Example 2, the average stacking number of WS2 phases in each sample in Examples 3-5 shows an increasing trend in the order of NiW / Ni-SAPO-11>NiW / Ni@SAPO-11>NiW / 4NiSAPO-11>NiW / SAPO-11, indicating that the interaction between the active phase and the support is weakened, which is conducive to the enhancement of the hydrogenation isomerization activity.
[0105] Table 3
[0106] Serial number catalyst i-C16 selectivity, % Comparative Example 1 NiW / SAPO-11-N 57.52 Comparative Example 2 NiW / SAPO-11 72.67 Comparative Example 3 NiW / SAPO-11-Ni 75.26 Example 1 NiW / 2NiSAPO-11 79.15 Example 2 NiW / 3NiSAPO-11 84.34 Example 3 NiW / 4NiSAPO-11 87.57 Example 4 NiW / / Ni&SAPO-11 83.89 Example 5 NiW / Ni-SAPO-11 90.51
[0107] The hydroisomerization catalysts prepared in Comparative Examples 1-3 and Examples 1-5 were used in the hydroisomerization reaction of n-hexadecane. The reaction results are shown in Table 3. Table 3 shows that the isomer selectivity of the hydrocarbon isomerization catalysts prepared in the present invention was increased by 21.63-32.99%, 6.48-17.84%, and 3.89-15.25%, respectively, compared to conventional hydrocarbon isomerization catalysts (Comparative Examples 1, 2, and 3), significantly outperforming the comparative examples. These results demonstrate that, compared to conventional hydroisomerization catalysts, the catalysts provided in the present invention have larger pore sizes and specific surface areas, higher Ni dispersion, higher isomerization selectivity, and exhibit excellent isomerization performance.
Claims
1. A hydroisomerization catalyst, wherein The invention comprises a Ni-modified SAPO-11 molecular sieve and an active component loaded thereon; the Ni-modified SAPO-11 molecular sieve has a pore size of 5.4 to 14.5 nm and a specific surface area of 195 to 288 m 2 / g, Ni dispersion is 0.31~0.
40.
2. The hydroisomerization catalyst according to claim 1, wherein The pore volume of the Ni-modified SAPO-11 molecular sieve is 0.27 to 0.5 m 3 / g; and / or, the active components are Ni and W.
3. The hydroisomerization catalyst according to claim 1 or 2, wherein The hydroisomerization catalyst is prepared by the following steps: Mixing a first nickel source, a first phosphorus source, a first aluminum source, and water to form a gel A1; adding a first structure directing agent and a first silicon source to the gel A1 to form a gel B1; subjecting the gel B1 to a first crystallization, and subjecting the product after the first crystallization to a first drying and a first calcination to obtain the Ni-modified SAPO-11 molecular sieve; The Ni-modified SAPO-11 molecular sieve is first impregnated with a first nickel-containing soluble salt solution and a first tungsten-containing soluble salt solution, and the product after the first impregnation is second dried and second calcined to obtain the hydroisomerization catalyst; Wherein, the first nickel source is calculated as NiO, the first aluminum source is calculated as Al2O3, and the weight ratio of the first nickel source to the first aluminum source is 0.01-0.04:1.0, preferably 0.03-0.04:1.
0.
4. The hydroisomerization catalyst according to claim 3, wherein The hydroisomerization catalyst is prepared by the following steps: mixing a second phosphorus source, a second aluminum source, and water to form gel A2; adding a second structure directing agent and a second silicon source to the gel A2 to form gel B2; subjecting the gel B2 to a second crystallization; and subjecting the product after the second crystallization to a third drying and a third calcination to obtain an intermediate product C2; subjecting the second nickel source and the intermediate product C2 to ion exchange, and subjecting the ion-exchanged product to a fourth drying and a fourth calcination to obtain the Ni-modified SAPO-11 molecular sieve; The Ni-modified SAPO-11 molecular sieve is subjected to a second impregnation with a second nickel-containing soluble salt solution and a second tungsten-containing soluble salt solution, and the product after the second impregnation is subjected to a fifth drying and a fifth calcination to obtain the hydroisomerization catalyst; The ion exchange treatment temperature is 70-95°C and the treatment time is 4-6 hours; The second nickel source is calculated as NiO, the second aluminum source is calculated as Al2O3, and the weight ratio of the second nickel source to the second aluminum source is 0.1-0.3:1.
0.
5. The hydroisomerization catalyst according to claim 4, wherein The hydroisomerization catalyst is prepared by the following steps: mixing a third phosphorus source, a third aluminum source, and water to form gel A3; adding a third structure directing agent and a third silicon source to the gel A3 to form gel B3; The gel B3 is subjected to a third crystallization; and the product after the third crystallization is subjected to a sixth drying and a sixth calcination to obtain an intermediate product C3; The intermediate product C3 is subjected to a third impregnation using a dispersion containing ethylenediaminetetraacetic acid and a third nickel source, and the product after the third impregnation is subjected to a seventh drying and a seventh calcination to obtain the Ni-modified SAPO-11 molecular sieve; impregnating the Ni-modified SAPO-11 molecular sieve with a third nickel-containing soluble salt solution and a third tungsten-containing soluble salt solution for a fourth time, and subjecting the product after the fourth impregnation to an eighth drying and an eighth calcination to obtain the hydroisomerization catalyst; The third immersion temperature is 20-40° C. and the immersion time is 4-6 hours. The third nickel source is calculated as NiO, and the weight ratio of the ethylenediaminetetraacetic acid, the third nickel source and the intermediate product C3 is 2-4:0.04-0.12:
1.
6. The hydroisomerization catalyst according to claim 5, wherein The first nickel source, the second nickel source and the third nickel source each independently include one or a combination of two or more of nickel nitrate, nickel acetate and nickel chloride; and / or, The first phosphorus source, the second phosphorus source and the third phosphorus source each independently include one or a combination of two or more of phosphoric acid, phosphorous acid and hypophosphorous acid; and / or, The first aluminum source, the second aluminum source, and the third aluminum source each independently include one or a combination of two or more of pseudo-boehmite, sodium aluminate, aluminum sulfate, and aluminum isopropoxide; and / or, The first structure directing agent, the second structure directing agent and the third structure directing agent each independently include one or a combination of two or more of di-n-propylamine, diisopropylamine, dimethylamine and diethylamine; and / or, The first silicon source, the second silicon source and the third silicon source each independently include one or a combination of two or more of silica sol, silicon dioxide and tetraethyl orthosilicate.
7. The hydroisomerization catalyst according to claim 5, wherein The first crystallization, the second crystallization and the third crystallization each independently include a first-stage crystallization, a second-stage crystallization and a third-stage crystallization performed sequentially; The treatment temperature of the first stage crystallization is 60-110°C and the treatment time is 12-14h; The treatment temperature of the second stage crystallization is 120-150° C. and the treatment time is 10-14 hours; The treatment temperature of the three-stage crystallization is 160-230° C., and the treatment time is 10-14 hours.
8. The hydroisomerization catalyst according to claim 5, wherein The treatment temperatures of the first calcination, the second calcination, the third calcination, the fifth calcination, the sixth calcination and the eighth calcination are each independently 500-700° C., and the treatment time is each independently 4-12 hours; and / or, The fourth calcination treatment temperature is 500-600° C., and the treatment time is 4-8 hours; and / or, The treatment temperature of the seventh calcination is independently 500-650° C., and the treatment time is 4-8 hours.
9. The hydroisomerization catalyst according to claim 5, wherein The nickel content in the first nickel-containing soluble salt solution, the second nickel-containing soluble salt solution and the third nickel-containing soluble salt solution is independently 2 to 6 wt % calculated as NiO; and / or The tungsten content in the first tungsten-containing soluble salt solution, the second tungsten-containing soluble salt solution and the first tungsten-containing soluble salt solution is independently 4 to 15 wt % in terms of WO 3 .
10. Use of the hydroisomerization catalyst according to any one of claims 1 to 9 in the isomerization reaction of normal paraffins.
Citation Information
Cited By
Preparation method of high-activity long-chain alkane isomerization catalyst
CN122032630A